Complete androgen insensitivity syndrome: A rare case report - Tushar Kambale; Payal Patel; Yaminy Pradeep Ingale; Charusheela Gore (Wolters Kluwer Medknow Publications, 2022)
Androgen receptor gene mutations on Xq12, which also have a 46XY karyotype abnormality, are the root cause of the X-linked uncommon recessive disorder of sex development known as androgen insensitivity syndrome (AIS). Complete AIS existed as a female, with normal breast, no uterus, ovaries, and fallopian tube with a blind-ending vagina but the presence of bilateral undescended testis either in the inguinal canal, abdomen, or labioscrotal junction and elevated testosterone levels. This was a rare case of a 22-year-old female patient who presented with primary amenorrhea. Ultrasonography showed gonads in the mid parts of inguinal canals on both sides, reaching up to the superficial ring. On investigation, increased in level of serum testosterone, follicle-stimulating hormone along with the luteinizing hormone was seen. AIS is actually very disturbing to individuals and families, so close collaboration between radiologist, pathologist, treating consultants, and psychiatrists are required for the proper management.